Prevalence of depression, anxiety, stress, and suicide tendency among individual with long-COVID and determinants: A systematic review and meta-analysis - Razieh Bidhendi-Yarandi; Akbar Biglarian; Jannike Lie Karlstad; Cathrine Fredriksen Moe; Enayatollah Bakhshi; Mohammad-Reza Khodaei-Ardakani; Samira Behboudi-Gandevani (PLoS ONE, 2025)
Background While mental health alterations during active COVID-19 infection have been documented, the prevalence of long-term mental health consequences remains unclear. This study aimed to determine the prevalence of mental health symptoms—depression, anxiety, stress, and suicidal tendencies—and to identify their trends and associated risk factors in individuals with long-COVID. Methods We conducted a systematic literature search of databases including PubMed, EMBASE, Scopus, CINAHL, Cochrane Library, Web of Science, and PsycINFO up to August 2024, targeting observational studies published in English. Study quality was assessed using structured standard tools. The primary outcome was the pooled prevalence of depression, anxiety, stress, and suicidal tendencies in individuals with long-COVID. Secondary outcomes included trends in these mental health problems over time and identification of associated determinants. Results A total of 94 eligible studies were included in the analysis. The pooled prevalence estimates, regardless of follow up times duration, were as follows: depression, 25% (95%CI:22–28%; PI:1–59%); anxiety (adjusted via trim and fill method), 23%(95%CI:21–25%;PI:2–35%); composite outcomes of depression and/or anxiety, 25% (95%CI:23–27%;PI:2–51%); stress, 26%(95%CI:13–39%;PI:1–69%); and suicidality, 19%(95%CI:15–22%;PI:13–25%). The results of meta-regression analyses revealed a statistically significant trend showing a gradual decrease in the prevalence of the composite outcome of anxiety and/or depression over time (RD = -0.004,P = 0.022). Meta-regression results indicated that being female and younger age were significantly associated with a higher prevalence of mental health symptoms. Study design and study setting did not contribute to heterogeneity. Conclusion One-fourth of individual with long-COVID experience mental health symptoms, including depression, anxiety, and stress, which remain prevalent even two years post-infection despite a slight decreasing trend. Factors such as female gender and younger age were linked to higher rates of anxiety and depression. These findings indicate the need for ongoing mental health screening and early interventions to mitigate long-term psychological distress in long-COVID patients.